2016
DOI: 10.1080/13880209.2016.1216131
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic potential of naringin: an overview

Abstract: Context: Naringin is a natural flavanone glycoside that is found in the Chinese herbal medicines and citrus fruits. Studies have demonstrated that naringin possesses numerous biological and pharmacological properties, but few reviews of these studies have been performed. Objective: The present review gathers the fragmented information available in the literature describing the extraction of naringin, its pharmacology and its controlled release formulations. Current research progress and the therapeutic potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
187
0
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 313 publications
(193 citation statements)
references
References 67 publications
1
187
0
5
Order By: Relevance
“…Flavonoids as naringin and hesperidin are widely distributed in Citrus species and are known to exhibit antioxidant, antiinflammatory, hepatoprotective, antineoplastic, thermogenic, and lipolytic effects (see, for example, Stohs et al ., ; Choi et al ., ; Lee et al ., ; Stohs and Badmaev, ; Chen et al ., ). Fujita et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Flavonoids as naringin and hesperidin are widely distributed in Citrus species and are known to exhibit antioxidant, antiinflammatory, hepatoprotective, antineoplastic, thermogenic, and lipolytic effects (see, for example, Stohs et al ., ; Choi et al ., ; Lee et al ., ; Stohs and Badmaev, ; Chen et al ., ). Fujita et al .…”
Section: Discussionmentioning
confidence: 97%
“…Flavonoids as naringin and hesperidin are widely distributed in Citrus species and are known to exhibit antioxidant, antiinflammatory, hepatoprotective, antineoplastic, thermogenic, and lipolytic effects (see, for example, Stohs et al, 2011c;Choi et al, 2015;Lee et al, 2015;Stohs and Badmaev, 2016;Chen et al, 2016). Fujita et al (2008) conducted a comparative evaluation of the inhibitory activity of 12 immature Citrus fruit extracts against cytochrome P450 isoforms and demonstrated that, although furanocoumarins are primarily responsible for inhibition of cytochrome P450, flavonoids are a contributing factor.…”
Section: Discussionmentioning
confidence: 99%
“…This compound shows a wide variety of pharmacological effects such as antioxidant, blood lipid-lowering and anticarcinogenic activity. Moreover, several studies have highlighted its potential to suppress the production of proinflammatory cytokines and attenuate the A C C E P T E D M A N U S C R I P T inflammatory response [7,8,9,10,11,12] and it has been proposed in combination with corticoids to treat skin diseases such as dermatitis [13].…”
Section: Introductionmentioning
confidence: 99%
“…Naringin is found in the white spongy portion of citrus peel. Its content varies from 0.65 mg g À1 in mandarin peel to 14.40 mg g À1 in grapefruit peel (Zhang, 2007;Hayat et al, 2010;Chen et al, 2016).…”
Section: Introductionmentioning
confidence: 99%